DISIPLIN DAN LOYALITAS TERHADAP KINERJA PEGAWAI PADA KANTOR DPRD PROVINSI PAPUA BARAT - Febry Jein Andjar; Nengsi Wosolo; Riana Elita Dewi Astuti Rehyaar (Universitas Gorontalo, 2020)
The purpose of this research is conducted: 1) To determine the effect of discipline on the performance of employees at the Office of the Provincial Parliament of West Papua. 2) To determine the effect of loyalty to employee performance at Parliament Office Porvinsi West Papua. This research is descriptive and correlation study using a quantitative approach. The population in this study as many as 56 employees of regional council offices in West Papua Province. The results showed that 1) Discipline positive effect on the performance of employees in the Office of the Provincial Parliament of West Papua. This is evidenced from tcount 4.703> ttable of 2.01290 with significant 0,000 <of a significance level of 0.05 and the regression coefficient has a positive value of 0.228. 2) Loyalty positive effect on the performance of employees in the Office of the Provincial Parliament of West Papua. This is evidenced from tcount of 7.417> ttable of 2.01290 with significant 0,000 <of a significance level of 0.05. and the regression coefficient has a positive value of 0.722. Keywords: Discipline, Loyalty, Employee Performance